The influence of leaf infusion administration of Angelica keiskei with Simvastatin on lowering triglyceride levels in Rattus norvegicus - Marentek, Cecilia Febriani; Ernawati, Ernawati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
Ashitaba is one from many plant that contained flavonoid. Flavonoid is antioxidant that belong to phenols. If we compare between ahitaba and vitamin C, ashitaba have hundred times more effective than vitamin c and twenty-five more effective then vitamin E. Antioxidant may reduce cholesterol by inhibiting oxidation reaction so that cholesterol can be easily pass through the arteries and its plug. This research aims to know what is the influence of ashitaba (Angelica keiskei) assisting simvastatinÂ  in lowering triglyceride levels in strain wistar white male rats (Rattus norvegicus) that in hypertriglycerid. The population on this research is strain wistar white rats (Rattus norvegicus), male, 100 g, 2 months age with health physical and total sample are 33 rats. The result from this research proved that there is no influence of ashitaba (Angelica keiskei) assisting simvastatin in lowering triglicyride levels in strain wistar white male rats (Rattus norvegicus) that in hypertriglycerid. It can caused by competituve reaction between ashitaba and simvastatin that they were blocking each other.